Weight Loss After Laparoscopic Sleeve Gastrectomy Ameliorates the Cardiac Remodeling in Obese Chinese - Meng, Weilun; Peng, Ronggang; Du, Lei; Zheng, Yixing; Liu, Diya; Qu, Shen; Xu, Yawei; Zhang, Yi (Frontiers in endocrinology (Lausanne), 2022)
This study aimed to investigate the impact of weight loss after laparoscopic sleeve gastrectomy (LSG) on cardiac structural and functional remodeling in obese Chinese. A total of 44 obese participants were enrolled consecutively. The physical, laboratory, electrocardiographic, and echocardiographic parameters of pre-and postoperative were recorded. The average follow-up time was 12.28 ± 5.80 months. The body mass index (BMI) of the patients with obesity was decreased from 41.6 ± 7.44 to 30.3 ± 5.73kg/m 2 ( P <0.001) after LSG. The systolic and diastolic blood pressure of the subjects was significantly reduced from 137.9 ± 15.7mmHg to 123.0 ± 16.0 and 83.4 ± 10.8 to 71.3 ± 11.7mmHg (P<0.001), respectively. The levels of fasting insulin and fasting blood glucose were significantly decreased (38.8 ± 32.1 to 8.43 ± 4.16 mU/L, P <0.001; 6.95 ± 2.59 to 4.64 ± 0.50mmol/L, P <0.001). Total cholesterol (TC, 4.66 ± 0.84 to 4.23 ± 0.75mmol/L, P<0.001) and triglyceride (TG, 1.92 ± 1.21 to 0.85 ± 0.30mmol/L, P<0.001) decreased significantly. Cardiovascular geometric parameters including aortic sinus diameter (ASD, 32.9 ± 2.83mm to 32.0 ± 3.10mm, P<0.05), left atrial diameter (LAD, 38.8 ± 4.03 to 36.2 ± 4.12mm, P<0.001), and interventricular septum thickness(IVS, 10.2 ± 0.93 to 9.64 ± 0.89mm, P<0.001) were significantly reduced. The ratio of weight loss (RWL) was positively correlated with the changes of LAD. The change of IVS was negatively correlated with the change of fasting blood glucose (GLU). Weight loss after LSG could effectively improve cardiac structural, but not functional, abnormality in obese Chinese.